2008
DOI: 10.1002/jcla.20223
|View full text |Cite
|
Sign up to set email alerts
|

Assay of ischemia‐modified albumin and C‐reactive protein for early diagnosis of acute coronary syndromes

Abstract: Diagnosis of cardiac ischemia in patients coming to emergency departments (ED) with symptoms of acute chest pain is often difficult. Many markers are sensitive and specific for the detection of myocardial necrosis but may not rise during reversible myocardial ischemia. Ischemia-modified albumin (IMA) has recently been shown to be a sensitive and early biochemical marker of ischemia. The variation laws were observed by measuring IMA and C-reactive protein (CRP) of 113 patients in ED within 12 hr after onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
3
16
2
2
Order By: Relevance
“…In those studies, the patients were not ''all comers,'' and the prevalence of ACS was unusually high in contrast to the real-life situation in a big city ED. 25,30,[33][34][35] We included in our study patients who were more representative of the population admitted to the ED with chest pain. 36 Contrary to previous studies, we studied patients with episodes of chest pain (persistent or not) suggesting a diagnosis of ACS to the EP, evolving within 12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, the patients were not ''all comers,'' and the prevalence of ACS was unusually high in contrast to the real-life situation in a big city ED. 25,30,[33][34][35] We included in our study patients who were more representative of the population admitted to the ED with chest pain. 36 Contrary to previous studies, we studied patients with episodes of chest pain (persistent or not) suggesting a diagnosis of ACS to the EP, evolving within 12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Kazanis et al (13) found higher IMA levels in stable CADs compared to healthy controls and TAS was lower in the CAD group. Besides the role of serum IMA levels in atherosclerotic heart disease (36,37), this marker may be beneficial in determining of diagnosis and mortality in such circumstances as acute mesenteric ischemia, cerebrovascular accidents, endstage renal disease, cardiopulmonary resuscitation, and pulmonary embolism (33,(38)(39)(40)(41). Although serum IMA levels were similar between SCF and control groups, we found a negative correlation between serum IMA levels and TAS in patients with SCF.…”
Section: Discussionmentioning
confidence: 66%
“…Frozen samples were mixed thoroughly after thawing and recentrifuged before analysis. Serum IMA was measured by ACB test (20) on the Hitachi analyzer 7170. H-FABP was measured by immunochromatography assay (Kang Sheng Bao Bioscience Corporation, Shenzhen, China).…”
Section: Laboratory Methodsmentioning
confidence: 99%